Einstein frequency of individual chalcogen bonds in Cu(In,Ga)Se2 and Cu(In,Ga)S2: Indicator of diffusion property of Cu, In, and Ga atoms - Kosuke Beppu; Fumiaki Amano; Seiji Yamazoe; Takahiro Wada (Next Materials)
Elucidating the characteristics of the Cu-Se, In-Se, and Ga-Se bonds in chalcopyrite-type Cu(In,Ga)Se2-based semiconductors can aid the design and fabrication of highly efficient thin-film photovoltaic devices. In this study, we used extended X-ray absorption fine structure (EXAFS) analyses to evaluate the characteristics of chemical bonds in Cu(In,Ga)Se2 and Cu(In,Ga)S2 powder samples at low temperatures (10–300 K). The temperature dependence of the structural and vibrational disorder (Debye–Waller factor) provides the Einstein temperature of an individual bond in Cu(In,Ga)Se2-based materials. The analyzed Einstein temperature, which is proportional to the Einstein frequency, increased in the order of Cu–Se(S) < In–Se(S) ≤ Ga–Se(S), and the S-containing bond had a higher Einstein temperature than the corresponding Se-containing one. We also analyzed the effect of the Ga/(Ga + In) ratio on the Einstein temperature of each chemical bond. The force constant of the oscillator (i.e., the bond) was determined from the Einstein frequency using the reduced mass of the constituent atoms. The obtained bond properties were found to correlate with the diffusion characteristics of the constituent atoms in CuInSe2-based solar cell materials.